Decolorization and detoxication of reactive industrial dyes by immobilized fungi Trametes pubescens and Pleurotus ostreatus - Casieri, L; Varese, G C; Anastasi, A; Prigione, V; Svobodová, K; Filippelo Marchisio, V; Novotný, C (Folia microbiologica, 2008)
Trametes pubescens and Pleurotus ostreatus, immobilized on polyurethane foam cubes in bioreactors, were used to decolorize three industrial and model dyes at concentrations of 200, 1000 and 2000 ppm. Five sequential cycles were run for each dye and fungus. The activity of laccase, Mn-dependent and independent peroxidases, lignin peroxidase, and aryl-alcohol oxidase were daily monitored during the cycles and the toxicity of media containing 1000 and 2000 ppm of each dye was assessed by the Lemna minor (duckweed) ecotoxicity test. Both fungi were able to efficiently decolorize all dyes even at the highest concentration, and the duckweed test showed a significant reduction (p < or = 0.05) of the toxicity after the decolorization treatment. T. pubescens enzyme activities varied greatly and no clear correlation between decolorization and enzyme activity was observed, while P. ostreatus showed constantly a high laccase activity during decolorization cycles. T. pubescens showed better decolorization and detoxication capability (compared to the better known P. ostreatus). As wide differences in enzyme activity of the individual strains were observed, the strong decolorization obtained with the two fungi suggested that different dye decolorization mechanisms might be involved.
Keywords: Bioreactors; Coloring Agents; Fermentation; průmyslový odpad; fermentace; textilní průmysl; Cells, Immobilized; Polyporales; Pleurotus; Textile Industry; bioreaktory; Industrial Microbiology; imobilizované buňky; Industrial Waste; Biodegradation, Environmental; biodegradace; barvicí látky; průmyslová mikrobiologie